Tanggung Jawab Notaris terhadap Akta Pernyataan Keputusan Rapat Umum Pemegang Saham yang Didasarkan pada Risalah Rapat Palsu - Rohidah Rohidah; Putra Hutomo; Yuliana Setiadi (Prodi Tata Negara (Siyasah) IAIN Langsa, 2025)
The Deed of Statement of Decisions of the General Meeting of Shareholders constitutes an authentic deed with perfect evidentiary value as regulated in Article 1868 of the Civil Code. In practice, there are still cases where a Deed of Statement of Decisions of the General Meeting of Shareholders is drawn up based on meeting minutes containing false information, which gives rise to legal problems concerning the legal consequences of the deed and the liability of the notary as a public official. This study aims to analyze the legal consequences of a Deed of Statement of Decisions of the General Meeting of Shareholders made on the basis of meeting minutes containing false information, as well as the forms of notarial liability arising from the preparation of such a deed. This research employs a normative legal research method using statutory and case approaches. The data used consist of secondary data in the form of laws and regulations, legal doctrines, and court decisions. The analysis is conducted using the theory of legal consequences and the theory of legal liability. The results of the study indicate that a Deed of Statement of Decisions of the General Meeting of Shareholders made on the basis of falsified meeting minutes remains valid as an authentic deed as long as it has not been annulled by a final and binding court decision. However, if it is proven to contain false information, the deed may be annulled and give rise to civil, criminal, administrative, and ethical liability for the notary. This study emphasizes the importance of the principle of prudence for notaries in examining meeting minutes and shareholder attendance lists in order to ensure legal certainty.